Association between Hasford Scoring System and Hematologic Response in Chronic and Accelerated Phase of Chronic Myelocytic Leukemia Patient with Imatinib for Three Months - Andy Purnomo; Ugroseno Yudho Bintoro; Made Putra Sedana; Ami Ashariati (Cell and BioPharmaceutical Institute, 2019)
Background: Hasford score is a scoring system which was made in interferon treatment era to assess chronic myelocytic leukemia (CML) prognosis. Complete hematologic response (CHR) is the milestone of prognosis evaluation. CHR achievement will significantly increase survival. Imatinib is a revolutionized treatment that change the prognosis of CML. With the advent of Imatinib, lessened the prognostic impact of the Hasford score to predict prognosis.Materials and Methods: An observational analytic with prospective cohort study conducted in oncology outward division Dr. Soetomo hospital Surabaya, from July until October 2018. Hasford score determined in 32 patients at the beginning of the study, given imatinib and followed up regularly for 3 months to know the hematologic response. Data were analyzed using Fisher exact test which was considered significant if p<0.05.Results: Median age was 39 years old, male 37.5% and female 62.5%, the median spleen was 18 cm, median hemoglobin was 9.1 g/dL, median leukocyte was 180x109 /L, median thrombocyte was 645x109 /L, median eosinophil was 2.9%, median basophil was 4.6%, median myeloblast was 6%. Hasford score showed 3.1% in low risk, 25% in intermediate risk and 71.9% in high risk. As much as 78.1% complete hematologic response was found in patient, and 21.9% was incomplete.Conclusion: There was no association between Hasford scoring system and hematologic response in chronic and accelerated phase of chronic myelocytic leukemia patient with imatinib for three month. Hasford score had no impact in hematologic response with imatinib.Keywords: Hasford score, hematologic response, CML, imatinib